ประสบการณ์การเป็นพยาบาลจบใหม่ที่ปฏิบัติงานในหอผู้ป่วยวิกฤต โรงพยาบาลมหาวิทยาลัย - กฤดิญาดา เกื้อวงศ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
The purpose of this study was to describe experiences of being a newly graduated nurse working at an intensive care unit of a university hospital by using qualitative research based on Heidegger phenomenology. Purposive sampling was used to select 14 nurse entrepreneurs who have been being the newly graduated nurses and experiences in ICU less than 3 years as informants were included and data were collected by using in-depth interviews with audio recordings. Data were analyzed by using content analysis van Manen’s method. The findings of the present research revealed the following five major emerging themes: 1. The reasons for deciding to work in an ICU, which consisted of the following five sub-themes: 1.1) Challenging workplace and life-long learning opportunities; 1.2) Better financial incentives; 1.3) Variety of educational and career paths; 1.4) Preferred work environment and style and 1.5) The good image and smart performance of critical care nurses. 2. In the beginning of actual work experience, many skill dimensions need improvement such as in the following four sub-themes: 2.1) Initial excitement and enjoyment in a new working atmosphere; 2.2) Need for time to adapt to the workplace; 2.3) Some communication problems requiring solutions and 2.4) Learning how to cope with death and dying. 3. During training, work under the supervision of mentors, which consisted of the following two sub-themes: 3.1) Learning about working from senior nurses and 3.2) Lack of understanding about real patient care situations. 4. Under real working circumstances, wrong decisions can be made, which consisted of the following five sub-themes: 4.1) Feelings of fear, inability to make decisions and fascination; 4.2) Feeling of sorrow and blame for inability to prompt detection of patients’ problems; 4.3) Feelings of regret for errors made in nursing care that potentially put patients in danger; 4.4) Working in a rush can lead to failure to exercise caution and meticulousness and 4.5) No knowledge about how to meet different objectives. 5. Reconsideration to stay or leave the unit involved, which consisted of the following two sub-themes: 5.1) To continue working, nurses need to work until they have confidence and 5.2) Some nurses should resign to seek new opportunities. According to the findings, newly graduated nurses are not ready to handle the provision of care in an ICU setting. Thus, nurse administrators should provide opportunities for newly graduated nurses to attend adequate training in critical care nursing before they start working in the ICU. Furthermore, for the initial period of their work in the ICU, nurses should be under the supervision of their mentors.